Swiss ethnoveterinary knowledge on medicinal plants – a within-country comparison of Italian speaking regions with north-western German speaking regions. Issue 1 (December 2017) - Mayer, Maria; Zbinden, Mirjam; Vogl, Christan; Ivemeyer, Silvia; Meier, Beat; Amorena, Michele; Maeschli, Ariane; Hamburger, Matthias; Walkenhorst, Michael
Abstract Background Ethnoveterinary knowledge in Europe may play an important role as a basis for sustainable treatment options for livestock. Aims of our study were (a) to compare the ethnoveterinary practices of two culturally and sociodemographically different regions of Switzerland, (b) to compare results with earlier ethnoveterinary studies conducted in Switzerland and in adjacent Italian regions and, (c) to evaluate possible reasons for regional differences in European ethnoveterinary medicine. Methods 25 interviews were conducted in 2014 in all Italian speaking regions (ItR) of Switzerland, and 31 interviews were held in five north-western German speaking Cantons (GeC). Semi-structured questionnaires were used to collect detailed information regarding plant species, mode of preparation, dosage, route of administration, category of use, origin of knowledge, frequency of use, and satisfaction with outcomes of the treatments. Results A total of 162 homemade remedies in ItR and 219 in GeC were reported, out of which 125 and 145, respectively, were reported to contain only one plant species (homemade single species herbal remedy report, HSHR). 44 ItR and 43 GeC plant species were reported to treat livestock, of which only a half were used in both regions. For each HSHR, we classified the treatment intention of all use reports (UR), leading to a total of 205 and 219 UR in ItR and GeC respectively. While cattle were the most often treated livestock species in both study regions, in ItR 40% of UR were administered to small ruminants. Main indications in both regions were gastrointestinal diseases and skin afflictions, but in ItR a high number of URs were reported as antiparasitics. URs were mainly handed down from the past generation, but in GeC the source of knowledge for 20% of URs were from courses. Regarding the used plant species, ItR showed a higher concordance with Swiss than Italian studies, but with some differences to all regions. A total of 22 (14 ItR; 8 GeC) plant species in this study have not been reported before in ethnoveterinary studies of Swiss and Italian alpine regions. Conclusions ItR and GeC, show differences and similarities with respect to their own ethnoveterinary practices and earlier Swiss and Italian ethnoveterinary studies. Linguistic, geographical, as well as social and farm-structural conditions influence the regional ethnoveterinary knowledge. However, political borders seem to be more important than language or geographical barriers.